2010
DOI: 10.1210/en.2010-0225
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Corticosterone Exposure Increases Expression and Decreases Deoxyribonucleic Acid Methylation of Fkbp5 in Mice

Abstract: There is evidence for hypercortisolemia playing a role in the generation of psychiatric symptoms and for epigenetic variation within hypothalamic-pituitary-adrenal (HPA) axis genes mediating behavioral changes. We tested the hypothesis that expression changes would be induced in Fkbp5 and other HPA axis genes by chronic exposure to corticosterone and that these changes would occur through the epigenetic mechanism of loss or gain of DNA methylation (DNAm). We administered corticosterone (CORT) to C57BL/6J mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
192
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(216 citation statements)
references
References 46 publications
14
192
1
2
Order By: Relevance
“…Thus, factors that facilitate FKBP51 expression could promote an environment in the aging brain that supports tau pathogenesis. We show that FKBP5 methylation is reduced both with age and in disease, which could be one factor leading to increased FKBP51 expression (54,57,58). FKBP5 methylation and FKBP51 expression appear to be inversely proportional over time.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, factors that facilitate FKBP51 expression could promote an environment in the aging brain that supports tau pathogenesis. We show that FKBP5 methylation is reduced both with age and in disease, which could be one factor leading to increased FKBP51 expression (54,57,58). FKBP5 methylation and FKBP51 expression appear to be inversely proportional over time.…”
Section: Discussionmentioning
confidence: 75%
“…Previous reports from the clinical literature have shown that methylation of the Fkbp5 gene (at the promoter region of exon 1) did not predict treatment response, but decreased in association with recovery (Yehuda et al, 2013). A study using a chronic corticosterone administration paradigm, that had been previously shown to result in a phenotype similar to chronic stress exposure (Gourley et al, 2009), induced an increase in Fkbp5 mRNA expression in the hippocampus, hypothalamus, and blood of mice with a correspondent decrease in DNA methylation at Fkbp5 intron 5 (Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation at functional glucocorticoid response elements in mouse Fkbp5 intron 5 described by Lee et al (2010) was performed based on procedures described by Sabbagh et al (2014), using Varionostic GmbH, Inc (Ulm, Germany, www.varionostic.de). Briefly, 500 ng genomic DNA was bisulfite-converted using the EZ-96 DNA methylation kit (Zymo, Irvine, CA).…”
Section: Dna Methylation Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Li et al (2015) did not detect a stress-related change in total methylation levels (i.e., 5-mC + 5-hmC), suggesting that the increase in 5-hmC was paralleled by a decrease in 5-mC, which collectively induced the stress-related NR3C1 upregulation. Stress exposure may additionally induce alterations in the epigenetic regulation of FK506 binding protein 5 (FKBP5), a known regulator of GR sensitivity (Binder 2009), as corticosterone administration during adulthood was shown to increase anxiety-like behaviour and elevate mouse hippocampal FKBP5 expression (and thus potentiate GR sensitivity) by decreasing DNA methylation at the Fkbp5 locus (Lee et al 2010). These findings collectively suggest that disrupted negative glucocorticoid feedback, as observed in PTSD, is characterized by elevated hippocampal and PFC GR levels, mediated by epigenetic mechanisms on the DNA and RNA level.…”
Section: Corticosterone Signallingmentioning
confidence: 99%